Komunikasi Politik Korporat Manchester United: Posisi Klub terhadap Isu-Isu Sosial, Rasisme, dan LGBTQ+ dalam Sepak Bola Modern - M. Ferdi Septianda (STISIP Widyapuri Mandiri Sukabumi, 2026)
This study analyzes the corporate political communication strategy of Manchester United in responding to contemporary social issues, specifically racism and LGBTQ+ rights. Using a qualitative approach with library research methods, this research examines how the club communicates its political positions through various platforms, manages conflicts of interest among diverse global stakeholders, and builds its image as a socially responsible organization. The findings reveal that Manchester United demonstrates a more consistent communication pattern on anti-racism issues through the